PERFORMANCE ANALYSIS OF PD/ZNO BASED FLEXIBLE UV MSM PHOTODETECTORS - Mowj R. Sabity; Ghusoon M. Ali (Journal of Engineering and Sustainable Development, 2022)
Flexible electronics and optoelectronics devices attract further attention in recent years. In this paper, we present the fabrication and photodetection properties of a flexible metal-semiconductor-metal UV photodetector based on a thin ZnO film with Pd Schottky electrodes. The active ZnO layer was created using a hydrothermal method on ITO/PET flexible substrates. Palladium employed as back-to-back Schottky contacts. Metal masks are designed and used to deposit palladium via thermal evaporation. To demonstrate the impact of ZnO on flexible substrates, the structural, optical, and electrical characteristics of the produced films were examined and assessed. I-V characteristics under dark and illumination conditions for a device were measured using a voltage range of -2.8 V to 2.8 V. The measured data were used to calculate device parameters and photodetection properties. Such as ideality factor, barrier height, saturation current, detectivity, responsivity, contrast-ratio, and efficiency. The proposed device exhibited a gain (efficiency of 200%} caused by trapping hole carrier at the ZnO-Pd interface.